Ностальгические мотивы в сонете Адама Мицкевича Аккерманские степи и их отражение в русских переводах - Козырева, Мария (Studia Rossica Posnaniensia, 2019)
The paper deals with the nostalgic motives in Adam Mickiewicz’s sonnet The Ackerman Steppe, expressed in the imagery of the poem, and their reflection in Russian translations, which were published in different periods from the 19th century up to our times. The author examined how the epoch and the translator’s position influenced the perception of the images.